Association of insulin-like growth factor 2 Apa1 A820G gene (rs680) polymorphism with polycystic ovarian syndrome - Thathapudi, Sujatha; Erukkambattu, Jayashankar; Addepally, Uma; Kodati, Vijayalakshmi; Hasan, Qurratulain (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hyperandrogenism is the cornerstone of polycystic ovarian syndrome (PCOS) as per androgen excess society - 2006 criteria. Insulin-like growth factor 2 (IGF 2) gene stimulates ovarian androgen secretion and is involved in the pathogenesis of PCOS. The objective of this study was to study the association of insulin-like growth factor 2 (IGF2) gene Apa1 A820G (rs680) polymorphism with PCOS. Methods: Prospective genetic case-control study, involving 204 women with PCOS and 204 healthy, sex and age matched controls. Anthropometric and biochemical profile were taken in a well-designed proforma. Isolation of deoxyribonucleic acid (DNA) by salting out method and genotype analysis was done for all the study population using PCR-RFLP. Results: We have demonstrated an association between IGF2 Apa1 A820G gene (rs680) polymorphism and PCOS. Frequency of G allele was 0.40 in PCOS and 0.08 in controls (OR 7.639, CI 5.08 to 11.47, and P value <0.0001) indicates that the G allele is associated with PCOS in our population. The GG genotype conferred a significant risk of developing PCOS (OR 19.645, CI 2.569 to 148.61 and P value 0.0039). We found the significant association of GG genotype with body mass index and insulin resistance in PCOS when compared with controls. Conclusions: This study suggests that IGF 2 gene Apa1 A820G polymorphism is associated with PCOS and could be used as a relevant molecular marker to identify women with risk of developing PCOS in our population and may provide an understanding about the etiology of PCOS.